2019
DOI: 10.3168/jds.2018-14974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of source on bioavailability of selenium, antioxidant status, and performance in lactating dairy cows during oxidative stress-inducing conditions

Abstract: In the current study, we used heat stress (HS) as an oxidative stress model to examine the effects of hydroxy-selenomethionine (HMSeBA), an organic selenium source, on selenium's bioavailability, antioxidant status, and performance when fed to dairy cows. Eight mid-lactation Holstein dairy cows (141 ± 27 d in milk, 35.3 ± 2.8 kg of milk/d, parity 2 or 3) were individually housed in environmental chambers and randomly assigned to 1 of 2 treatments: inorganic Se supplementation (sodium selenite; SS; 0.3 mg of Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 33 publications
6
44
2
Order By: Relevance
“…Se exists in the form of selenoproteins (Sels) that play important biological function in dairy cows [13]. The upregulated GPX mRNA expression and GSH-PX activity that we detected indicated that Sel expression of mammary regulated the activities of milk Se-containing enzyme.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Se exists in the form of selenoproteins (Sels) that play important biological function in dairy cows [13]. The upregulated GPX mRNA expression and GSH-PX activity that we detected indicated that Sel expression of mammary regulated the activities of milk Se-containing enzyme.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies found that dietary Se has no significant effect on milk yields and components [25,26]. On the contrary, other studies found that Se may result in lower milk protein [27], decreased milk fat [13] and higher milk yields [28]. These results could be due to differences in Se forms and doses/or the composition of the diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activities of glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and concentration of maleic dialdehyde (MDA) were analyzed using respective commercial kits (Nanjing Jian Cheng Bioengineering Institute, Nanjing, China) as described previously [28]. The inter-assay CVs of SOD, MDA, and GSH-Px were 1.57, 3.28, and 3.21, respectively, and the intraassay CVs of SOD, MDA, and GSH-Px were 3.64 Samples of MR and starter were collected once per week, and the content of DM, crude protein (CP), ash, ether extract (EE), acid detergent ber (ADF), neutral detergent ber (NDF), calcium (Ca), and phosphorus (P) were determined as described in a previous study [29]. The content of protein, fat, lactose, total solids, and non-fat solids of the milk was determined with the mid-infrared procedures using a Milk Oscan Minor machine (MilkoScan Type 78110; Foss Electric, Hillerød, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…In ruminant species the assimilation of Se from the diet can be dependent upon rumen conditions that can substantially decrease the availability of mineral forms of Se, in particular sodium selenite [10]. Organic forms of Se do not appear to suffer the same ruminal fate as mineral forms, and as such, would be more available for utilization by dairy cows [11,12]. Therefore, the aim of the current review is to critically analyze existing knowledge on the role of organic Se in dairy cow nutrition with specific emphasis on commercially relevant stresses.…”
Section: Introductionmentioning
confidence: 99%